2010
DOI: 10.1002/ceat.200900234
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of Water Droplets in Crude Oil Emulsions: Analytical Solution

Abstract: In petroleum refineries, water is used in desalting units to remove the salt contained in crude oil. Typically, 7 % of the volume of hot crude oil is water, forming a water-and-oil emulsion. The emulsion flows between two electrodes and is subjected to an electric field. The electrical forces promote the coalescence of small droplets of water dispersed in crude oil, and these form bigger droplets. This paper calculates the forces acting on the droplets, highlighting particularly the mechanisms proposed for dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 6 publications
(8 reference statements)
2
16
0
Order By: Relevance
“…The effect on the inlet flow rate of fresh water showed similar results to that of Aryafard et al [13]. Bresciani et al [7] proposed a mechanism for droplet-droplet collision and coalescence in the presence of an external electric field. A model was developed to determine the time between collision and displacement speed of water droplets considering the forces acting on the droplets.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…The effect on the inlet flow rate of fresh water showed similar results to that of Aryafard et al [13]. Bresciani et al [7] proposed a mechanism for droplet-droplet collision and coalescence in the presence of an external electric field. A model was developed to determine the time between collision and displacement speed of water droplets considering the forces acting on the droplets.…”
Section: Introductionsupporting
confidence: 78%
“…Additionally, the geometry of such electrostatic desalting unit is extremely complex. Desalting of crude oil involves two steps, the first is to mix the oil stream with a stream of freshwater intensively, which results in reducing the stability of the water-in-oil emulsion and the second is to separate the saline water present in the emulsion [7,8]. Depending on the amount of gas, salt and water present in the extracted crude oil, two different separation techniques are used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation results demonstrated that the emulsion will form droplets of larger diameter through a filter with larger pore spacing, but it is difficult for the larger-diameter droplets to coalesce; thus, it is difficult to separate water and oil [ 18 ]. Bresciani et al [ 19 ] investigated the effect of the electric field on the coalescence mechanism of droplets, and a mathematical model was established to calculate the collision velocity and the coalescence time of the droplet. The results indicated that the coalescence of droplets could be accelerated by changing operating parameters such as temperature and electric field.…”
Section: Introductionmentioning
confidence: 99%